(untitled) (Scientia Agropecuaria, 2013)
The objective of this study was to evaluate the incidence and influence of stalk rot and ear in cultivation of hybrid corn second crop in west region Paraná. The experiment was conducted in randomized block design with six transgenic corn hybrids (DKB 330PRO, P4285HX, P3646HX, 30F53HX, P3340HX and P3161HX) with four replications at spacing of 0.90 m between rows and 0.20 m between plants. The characteristics evaluated were: number of healthy and symptomatic plants, number of ears healthy and symptomatic and total number of spikes. After harvest, we assessed the length of ears healthy and symptomatic, bulk grain ears healthy and symptomatic, thousand grain weight of ears healthy and symptomatic, and grain mass per spike weighted, thousand grain weight and weighted productivity. The hybrid P3646HX showed 100% of plants with stem base rot (Colletotrichum graminicola) and soft rot cob (Erwinia chrysanthemi pv. Zeae) and 100% of ears with symptoms of soft rot, followed by hybrid 30F53HX, DKB 330PRO with 34.9 and 29.1% of ears with symptoms of soft rot respectively. The hybrid DKB330PRO showed healthy spikes and patients with superior size, resulting in less interference in the grain yield. The hybrid P3340 productivity was higher, with 7952 kg ha-1 , followed by hybrid 30F53HX and DKB330PRO. A positive correlation between agronomic characteristics and grain yield.